Internet of Things Scholarship (2010–2026): A Scopus-Based Bibliometric Review of Thematic Clusters and Research Fronts - Judijanto, Loso; Triwiyatno, Aris; Winardi, Bambang (West Science Information System and Technology, 2026)
With the fast development of the digital world, the Internet of Things (IoT) has become an important element in the research domain nowadays. This research seeks to explore how the IoT literature developed from 2010 to 2026 via the bibliometric analysis of publications in Scopus databases. Using VOSviewer software to analyze co-authorship network, citation network, and keywords co-occurrence network, this study is intended to illustrate the structural features of the IoT literature in terms of its intellectural, social, and conceptual aspects. The findings indicate that IoT studies are characterized by close relations between researchers around the world, resulting in several major knowledge diffusion centers. In the context of citations analysis, the major sources not only contribute to technological development but also address issues like the sustainable environment, digital governance, and socio-economic transformations. As regards keywords co-occurrence analysis, the main groups of IoT research are smart environments, technology, engineering, and socio-technical studies. Overlay and density maps point out that there is a change in time concerning the focus of research towards more advanced concepts in the field, such as artificial intelligence in IoT, big data analysis, industry 4.0, and sustainable development. It can be concluded that IoT research is becoming more mature and multidisciplinary in nature, focusing more on addressing issues on a global scale. This paper will contribute to the existing literature on IoT research through a thorough systematic and long-term analysis of IoT studies.